2009
DOI: 10.2967/jnumed.108.057703
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Interim 18F-FDG PET in Patients with Diffuse Large B-Cell Lymphoma: SUV-Based Assessment at 4 Cycles of Chemotherapy

Abstract: Interim 18 F-FDG PET (after 1-4 cycles of chemotherapy) may be useful for tailoring a risk-adapted therapeutic strategy in lymphoma. The purpose of this study was to investigate whether semiquantification of standardized uptake values (SUVs) may help to improve the prognostic value of 18 F-FDG PET, compared with visual analysis, after 4 cycles of chemotherapy. Methods: In a previous report, we showed that a 65.7% reduction in maximal SUV (SUVmax) between baseline (PET0) and 2 cycles of chemotherapy (PET2) bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
126
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(131 citation statements)
references
References 14 publications
2
126
0
3
Order By: Relevance
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,38 All of these variables, which are often taken into consideration in the same report, can modify and alter the results significantly; consequently, data obtained from interim PET evaluations performed at different observation periods should not be pooled. Furthermore, the potential different response related to the inclusion or exclusion of rituximab in the treatment regimen must be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor glucose metabolism measured by FDG PET has been reported to be valuable in predicting the outcome of many cancers, such as head and neck squamous cell carcinoma [6][7][8], lymphoma [9][10][11], and esophageal [12] and lung cancers [13]. However, studies on the prognostic value of FDG PET in endometrial cancer are limited.…”
Section: Introductionmentioning
confidence: 99%